A concepção de cooperação das equipes do Serviço de Atendimento Móvel de Urgência (SAMU) - Yana Thamires Mendes Felix; Anísio José da Silva Araújo; Thaís Augusta Cunha de Oliveira Máximo (Universidade do Porto, 2019)
This paper aims to analyze the cooperation in the Mobile Emergency Care Service (SAMU) of a Brazilian city from the perspective of the workers. The theoretical references include the debate on the cooperation developed by the Work Psychodynamics and by some Sociology authors. The study consisted of holding collective interviews with twenty-four SAMU workers. The data was analyzed through the Thematic Content Analysis and the results evidenced the cooperation as determinant in the SAMU service, since the ability to work in a coordinated way results in the efficiency of the service rendered. There are also reflections on strengthening the bonds between workers, mitigating the hierarchical rigidity that characterizes certain health organizations. The exchange of experiences as a way to improve coping with emergencies is a common practice among workers, reinforcing the relevance of cooperation in SAMU service.